STUDY OF COAL GASIFICATION REACTIVITY IN MEULABOH AND TANJUNG ENIM USING THE APPROACH THERMOGRAVIMETRIC ANALYSIS (TGA) - Junior, Nicko
Coal is one of the main energy sources in Indonesia. Utilization of fuel derived from coal has been done through conventional method which relatively less clean. Utilization of coal in Indonesia can be further developed to be cleaner through gasification process. One of the important parameters to pay attention is gasification reactivity. The coal samples used in this study were taken from Meulaboh, Aceh (AG1) and Tanjung Enim, South Sumatra (AG2). Gasification reactivity determination was carried out based on focused thermogravimetric analysis to observe the thermal characteristics of the pyrolysis and gasification processes. During thermogravimetric analysis the samples were programmed to be heated from 50? C to 900? C with a heating rate of 10? C/min in argon atmosphere. Subsequently, the samples were hold for 10 minutes at 900? C to obtain an isothermal state state. Finally, the samples were analyzed in a mixture atmosphere (25% air and 75% argon). Characteristics of coal samples AG1 and AG2 were obtained from the results of proximate and calorie values analyses. The AG1 coal sample is classified as Sub-bituminous C and the AG2 sample is classified as high-volatile C bituminous. The TG/DTG thermogram curve indicates that both samples underwent pyrolysis and gasification processes. During the gasification process, the AG1 sample showed a greater decrease in mass so that its reactivity was greater compared to that of AG2 sample. Low rank coal is more reactive because it has more functional group compounds with higher oxygen content, more porous structure, and larger area of active surface.